2019
DOI: 10.3390/nu11020300
|View full text |Cite
|
Sign up to set email alerts
|

Passive Commuting and Higher Sedentary Time Is Associated with Vitamin D Deficiency in Adult and Older Women: Results from Chilean National Health Survey 2016–2017

Abstract: The aim was to investigate the associations between different physical activity (PA) patterns and sedentary time (ST) with vitamin D deficiency (<12 ng/mL) in a large sample of Chilean women. In this cross-sectional study, the final sample included 1245 adult and 686 older women. The PA levels, mode of commuting, ST, and leisure-time PA were self-reported. Vitamin D deficiency was defined as <12 ng/mL and insufficiency as <20 ng/mL. A higher ST was associated with vitamin D deficiency (odds ratio (OR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…In the Southern Hemisphere, Chile and Argentina have significant portions of the country residing above 37 o . Both have vitamin D supply estimates from natural food sources in the range of 3.1 to 5.5 µg/day, and reported prevalence of vitamin D deficiency of 14-26% overall and higher in the Southern regions of the country (higher latitudes) [41,42]. These Northern and Southern Hemisphere countries residing at >37 o broadly track to upper middle to high income settings and as such have relatively good supply of foods of animal origin, key providers of vitamin D in the food chain.…”
Section: Discussionmentioning
confidence: 99%
“…In the Southern Hemisphere, Chile and Argentina have significant portions of the country residing above 37 o . Both have vitamin D supply estimates from natural food sources in the range of 3.1 to 5.5 µg/day, and reported prevalence of vitamin D deficiency of 14-26% overall and higher in the Southern regions of the country (higher latitudes) [41,42]. These Northern and Southern Hemisphere countries residing at >37 o broadly track to upper middle to high income settings and as such have relatively good supply of foods of animal origin, key providers of vitamin D in the food chain.…”
Section: Discussionmentioning
confidence: 99%
“…Higher triglycerides as a metabolite class were significantly inversely associated with XFG, which is in contrast to findings from multiple cross-sectional studies that observed positive associations with XFG. [64][65][66][67][68] Although we adjusted for caffeine intake and recreational physical activity, lower triglycerides in cases may be capturing residual information about greater coffee consumption 69 or lower sedentary behavior and greater physical activity, 70,71 which are likely associated with higher homocysteine levels and greater UV exposure, 72 respectively, and higher XFG risk. Also, as higher triglyceride levels are a component of metabolic syndrome, it could also be a proxy for greater hyperglycemia, which may have protective effects against the accumulation of XFM.…”
Section: Lysophosphatidylcholines (Lpcs)mentioning
confidence: 99%
“…The question was, "How much time do you usually spend sitting or reclining on a typical day (hours and minutes per day)?" Based on previous studies [25], the high (≥240 min/day) or low levels of ST (<240 min/day) were identified.…”
Section: Classification Of Physical Activity and Sedentary Timementioning
confidence: 99%